2014
DOI: 10.1016/j.biomaterials.2013.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Control of angiogenesis by VEGF and endostatin-encapsulated protein microcrystals and inhibition of tumor angiogenesis

Abstract: Encapsulation of cytokines within protein microcrystals (polyhedra) is a promising approach for the stabilization and delivery of therapeutic proteins. Here, we investigate the influence of vascular endothelial growth factor (VEGF) microcrystals and endostatin microcrystals on angiogenesis. VEGF was successfully encapsulated into microcrystals derived from insect cypovirus with overexpression of protein disulfide bond isomerase. VEGF microcrystals were observed to increase the phosphorylation of p42/p44 MAP ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…We previously showed that the activity of cytokines encapsulated in polyhedra, which are protein microcrystals of cypovirus, can be stably maintained over long periods in both ex vivo and in vivo environments, and can be slowly released to stimulate the growth and differentiation of many cell types continually (14,(24)(25)(26)(27)(28)(29). Therefore, to determine whether sericin hydrogels can act as scaffolds to support cell growth and differentiation, we cultivated the mouse embryonic stem (ES) cell line EB5 on sericin hydrogels that were overlaid with a medium containing canonical recombinant human leukemia inhibitory factor (rhLIF) or that incorporated polyhedron-encapsulated LIF (24) (SI Appendix, SI Materials and Methods).…”
Section: Expression and Physiological Effects Of Truncated P1a In Silmentioning
confidence: 99%
“…We previously showed that the activity of cytokines encapsulated in polyhedra, which are protein microcrystals of cypovirus, can be stably maintained over long periods in both ex vivo and in vivo environments, and can be slowly released to stimulate the growth and differentiation of many cell types continually (14,(24)(25)(26)(27)(28)(29). Therefore, to determine whether sericin hydrogels can act as scaffolds to support cell growth and differentiation, we cultivated the mouse embryonic stem (ES) cell line EB5 on sericin hydrogels that were overlaid with a medium containing canonical recombinant human leukemia inhibitory factor (rhLIF) or that incorporated polyhedron-encapsulated LIF (24) (SI Appendix, SI Materials and Methods).…”
Section: Expression and Physiological Effects Of Truncated P1a In Silmentioning
confidence: 99%
“…This technique was applied to immobilize various cytokines, such as FGF, LIF, and EGF in PhCs. 126,127 These immobilized cytokines retain their biological activities, which include promotion of fibroblast growth and proliferation of mouse embryonic and induced pluripotent stem cells by slow release of the immobilized proteins.…”
Section: In Vivo Crystal Engineeringmentioning
confidence: 99%
“…3B). Tube formation is a key step for angiogenesis in vitro 26, 27 . To investigate the angiogenic effect of 5%CS/β-TCP scaffolds on HUVECs, cells were seeded on Matrigel in the lower chamber with 5%CS/β-TCP or β-TCP in transwell inserts.…”
Section: Resultsmentioning
confidence: 99%